Analysis of the Role of Gross Profit as an Indicator of Operational Financial Performance: A Qualitative Case Study of PT Astra Agro Lestari Tbk - Vidhini Nazhifa Rachmalimy; Asri Sundari; Evi Karyani; Marintan Anastasya Putri; Silvia Ananda Putri; Nisrina Salma Putri (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze changes in gross profit and its components in assessing the financial performance of PT Astra Agro Lestari Tbk. Research Method: This study employed a quantitative descriptive design based on a documentary review. Data were obtained from the interim consolidated financial statements for the three-month periods ending March 31, 2025, and March 31, 2024, and were then analyzed using comparisons, ratios, and arithmetic decomposition. Results and Discussion: Net revenue increased by 46.33%, cost of revenue rose by 44.31%, and gross profit grew by 60.99% to Rp937,287 million. The gross profit margin increased from 12.13% to 13.34%. Of the increase in gross profit, 75.97% was attributable to revenue growth and 24.03% to improved margins. The 21.95% decrease in inventory does not demonstrate successful sales timing, while the 7.34% increase in depreciation does not demonstrate modernization without supporting investment data. Implications: Gross profit should be evaluated in conjunction with volume, selling price, unit cost, inventory, and cash flow to avoid overestimating efficiency. Originality: The study provides a breakdown of gross profit and distinguishes between accounting facts and managerial interpretations in the palm oil industry.